Digital Leadership Competency Framework in Construction: The Case of Entry-Level Positions - Risath Athamlebbe; Rahimi A. Rahman (Journal of Engineering, Project, and Production Management, 2025)
The construction industry, which is vital to the global economy, stands poised to enhance its impact through digitalisation in the Construction 4.0 era. However, the pace of digital transformation is hindered by employee competency gaps and ineffective leadership. Developing digital leadership (DL) competencies within its workforce is crucial if the construction industry is to navigate this transformation effectively. Entry-level positions in the construction industry play a crucial role, and DL competencies in these positions are necessary to support digital transformation. Despite this importance, the specific DL competencies required for entry-level positions in the construction industry have not been explored in the literature. This study aimed to develop a DL competency framework that is tailor-made for entry-level positions in terms of knowledge, skills, and attributes. Data were collected through semi-structured interviews with construction industry professionals from Malaysia and Sri Lanka. Thematic analysis was used to analyse the data. The framework developed includes three main knowledge themes: digital, technical, and sustainable project management, along with eight sub-themes. Skills comprises three main themes: managerial, technical, and interpersonal, together with six sub-themes. Finally, attributes have two main themes, professional and personal, with six sub-themes. Furthermore, the analysis suggests that these identified themes and sub-themes are common across Malaysia and Sri Lanka. The findings indicate that it would be possible to develop a DL competency framework aligned at a global scale. This is the first study to develop a DL competency framework that is tailor-made for entry-level positions in construction, so it offers foundational insights for research, practical applications, educational upgrades, organisational readiness, and policy formulation to enhance digital transformation.